2005
DOI: 10.1111/j.1365-2621.2005.tb11524.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Lactobacillus casei KCTC 3260 to Reactive Oxygen Species (ROS): Role for a Metal Ion Chelating Effect

Abstract: The antioxidative capacity of 4 Lactobacillus strains, isolated from a milk product, was evaluated by measuring total antioxidative ability (TAA) and resistance to reactive oxygen species (ROS). Both intact cells and intracellular cell‐free extracts of Lactobacillus casei KCTC 3260 demonstrated the highest antioxidative activity and inhibited lipid peroxidation by 46.2% and 72.9%, respectively. To evaluate the resistance of 4 Lactobacillus strains to ROS, we tested the survival under conditions of 1 mM hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 21 publications
2
63
1
Order By: Relevance
“…(Kullisaar et al 2002;Lee et al 2005). High consistency between TGSH and TAA-CFE was observed (r>0.8) and was in agreement with Zanoni et al (2008), and high correlation was observed between TAA (IC, CFE) and TLA (CFE) values (r>0.8).…”
supporting
confidence: 84%
See 3 more Smart Citations
“…(Kullisaar et al 2002;Lee et al 2005). High consistency between TGSH and TAA-CFE was observed (r>0.8) and was in agreement with Zanoni et al (2008), and high correlation was observed between TAA (IC, CFE) and TLA (CFE) values (r>0.8).…”
supporting
confidence: 84%
“…However, these measures did not correlate with each other ( Table 2). The inhibition of ascorbic acid autoxidation and linoleic acid peroxidation is commonly used to determine the total antioxidative activity of LAB and probiotics (Lee et al 2005;Lin and Chang 2000;Zanoni et al 2008). The ascorbate autoxidation system could also be used to test for the presence of extraneous catalytic metals in aqueous solution because the rate of ascorbate oxidation strongly depended on the catalytic metals in the aqueous solution (Buettner 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the nine completed genome sequences of bifidobacteria do not reveal any SOD-related genes. The discrepancy may be explained by the proposal that SOD activity measurements in bifidobacteria were probably false-positive results, based on comparisons with known SOD enzymes (42,160). This proposal is supported by the genome analysis.…”
Section: Stress Responsementioning
confidence: 50%